2016
DOI: 10.21315/aamj2016.21.supp.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effects of Environmental Components on Tourism Destination Competitiveness: The Moderating Impact of Community Support

Abstract: Contemporarily, tourism sector is a highly competitive environment, which forces tourism players to provide better visitor services in order to stay competitive. In rural tourism, a growing niche in the tourism market, multiple components of environmental constructs play a crucial role in contributing to the sustainability and competitiveness of rural tourism destinations. Hence, this study examines the impact of environment components on development of rural tourism destination competitiveness from a local co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 95 publications
(139 reference statements)
0
4
0
Order By: Relevance
“…Additionally, taking South-East Asian countries as examples, Brahmasrene and Lee [30] discovered that the tourism industry could inhibit carbon emissions, and that ecotourism was effective. Furthermore, Chin et al [31] studied the impact of the environment on the development of tourism in Malaysia, and found that a quality ecological environment would promote the competitiveness of rural tourism destinations effectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, taking South-East Asian countries as examples, Brahmasrene and Lee [30] discovered that the tourism industry could inhibit carbon emissions, and that ecotourism was effective. Furthermore, Chin et al [31] studied the impact of the environment on the development of tourism in Malaysia, and found that a quality ecological environment would promote the competitiveness of rural tourism destinations effectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(Rosciano, et al, 2013;Blancas et al, 2015). Scientific studies have also been dedicated to identifying key target groups and stakeholders within tourism, encompassing both internal and external stakeholders, such as DMOs (Dias et al, 2021), both domestic and foreign visitors (Zeng et al, 2021;Xu et al, 2021, Jangra et al, 2021, members of the local community (Chee-Hua et al, 2016;García-Almeida & Gartner., 2021;Lai et al, 2021) as well as experts and members of academia (Wong et al, 2008;Blancas et al, 2015) and representatives of public and private sectors within the destinations (Goffi & Cucculelli, 2019;Ndivo & Manyara., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, degradation may happen to part of natural resources due to the increasing number of tourists in that particular tourism destination (Chin et al, 2016). Moreover, the minimum of resource space carrying capacity, tourism economic development carrying capacity, social carrying capacity and ecological environmental capacity help to define the amount of tourism activities of a destination (Du & Pu, 2013).…”
Section: Carrying Capacitymentioning
confidence: 99%
“…Additionally, past researchers such as Tang et al (2013) have underlined the substantial role of a destination related to tourism as the spatial carrier of tourism as the carrying capacity of that particular destination does affect the sustainability of relevant destination and competitiveness in the long run (Chin et al, 2016). Nevertheless, the increasing number of visitors to the destination may cause issues such as overcrowding which can lead to the reduced quality of experience during their visitations (Thong et al, 2019).…”
Section: Introductionmentioning
confidence: 99%